POPULATION DYNAMICS OF SILVERBELLY LEIOGNATHUS JON ESI IN PALK BAY - Venkataraman, G; Badrudeen, M; Thiagarajan, R (Indian Journal of Fisheries, 2011)
Based on catoh, effort and length-distribution data on Leiognathus jonesi collected at Mandapam over a period of sk seasons, age and growth, selection factor, coefficient of total mortality (Z) and coefficient of natural mortality (M) were derived1. For the estimated’ natural mortality rclte (2.1) and for the mesh size (25 mm codend) now in operation, the optimum effort has been found to bs 50,000 standard night effort, (= 5,000 std. day effort), the yield per hundred recruits being 310 g. The isopleth diagram indicates that there was overfishing of silverbellies in 1973-74 and 1974-75 when the effort far exceeded the optimum level. The isopleth diagram also shows that the present mesh size yields the best catch and an increase in mesh size to 35 mm or decrease to 15 mm leads only to a decrease in yield. For a scientific rwanagetnemt of the fishery, it is suggested that the effort be maintained at 50,0000 night standard effort with the present mesh size at 25 mm so as to obtain sustained yield of this fish in the coming years.